2015
DOI: 10.1016/j.proeng.2015.11.335
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Suction/Injection on Free Convection in a Micropolar Fluid Saturated Porous Medium under Convective Boundary Condition

Abstract: In this article, the influence of the convective boundary condition of free convection flow over a permeable vertical plate in porous medium saturated with a micropolar fluid is investigated. In order to analyze all the essential features, the transformed nonlinear conservation equations are worked out numerically by Spectral Quasi-Linearisation Method. By insisting the comparison between suction and injection effects, the physical quantities of the flow and its characteristics are exhibited graphically and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They found that fluid velocity decreases with increasing suction/injection parameter. Ram-Reddy and Pradeepa 5 solved numerically suction/injection on a free convection under convective boundary condition using Spectral Quasi-Linearization Method. Their work revealed that skin friction and heat and mass transfer increases as a result of increase in both cases of suction and injection.…”
Section: Introductionmentioning
confidence: 99%
“…They found that fluid velocity decreases with increasing suction/injection parameter. Ram-Reddy and Pradeepa 5 solved numerically suction/injection on a free convection under convective boundary condition using Spectral Quasi-Linearization Method. Their work revealed that skin friction and heat and mass transfer increases as a result of increase in both cases of suction and injection.…”
Section: Introductionmentioning
confidence: 99%
“…They found that as the suction/injection parameter increase, the velocity and temperature profiles as well as the rate of heat transfer decrease. Since then, many researchers have been working on the suction or injection effect with various physical conditions [see Ahmad (2016), Ganapathirao and Ravindran (2017), Hamid et al (2017), Maity et al (2016), Mohamed et al (2016), Naramgari and Sulochana (2016), Pandey and Kumar (2016), Ramesh Babu et al (2016), RamReddy and Pradeepa (2015), Rizwan-Ul-Haq et al (2016), Zaidi and Mohyud-Din (2016) and Zeeshan and Majeed (2016)].…”
Section: Stability Analysis On Stagnationpoint Flowmentioning
confidence: 99%